PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT TAHUN 2007-2011 - SETIANI B01108063, TRI AGUS (Jurnal Pembangunan dan Pemerataan, 2014)
Thesis with the title "Against the Effects of Fiscal Decentralization Economic Growth In West Kalimantan Province". The purpose of this study was to analyze the influence of Fiscal Decentralization on economic growth districts / cities in West Kalimantan 2007-2011. This study aims to determine how the effect of the original income variable, the General Allocation Fund, Special Allocation Fund, Revenue Sharing, to economic growth and city districts in West Kalimantan 2007-2011. This study uses a quantitative method using secondary data in the form of panel data. Research area is the entire county and city in West Kalimantan 2007-2011.The results of this study indicate that the original income and no significant positive effect on economic growth with a coefficient value of 0.000326, the General Allocation Fund and significant negative effect on economic growth with a coefficient value of 0.005497, the Special Allocation Fund to the value of the coefficient of 0.013144 and DBH positive effect and significant impact on economic growth in the value of the coefficient of 0.049734.Local governments are expected to further optimize the allocation of the original income funds, General Allocation Fund, the Special Allocation Fund and Revenue Sharing to be better implemented regional development, which in turn can spur economic growth in the higher regions from year to year. Â  Keywords: Fiscal Decentralization, Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), DBH (DBH).